Sistem Informasi Praktek Kerja Industri (Prakerin) Studi Kasus SMK Pariwisata Mataram - I Made Sulastra; lalu A. Syamsul Irfan Akbar; Suthami Ariessaputra (JEITECH (JOURNAL OF ELECTRICAL ENGINEERING AND INFORMATION TECHNOLOGY), 2024)
The Mataram Tourism Vocational High School still uses a manual system to process data internships for student, teacher, and Prakerin information. An information system is an essential instrumentation to monitor internship implementation. To overcome this problem, a Prakerin Information System was designed and built in this study to help simplify the administrative process of student internships while monitoring its implementation. The Prakerin information system also provides information about Prakerin needed by students and an application form for Prakerin online. In this study, the author uses several methods of data collection, namely observation with data objects, namely at Mataram Tourism Vocational High School, interviews with communication approaches that relate directly to data sources, and literature studies by collecting data by looking for literature about the task to this end. The authors used Python and MySql programming languages, the Bootstrap Framework, and the Django Framework in this study.. The results of testing using the Black box method with 93% success and the method of Mean Opinion Score (MOS) with a score of 4.01. This research resulted in an information system of Mataram Tourism Vocational Industry Practices that helped the administrative process of engineering, such as registration of internships, student data input, school supervisor data, field supervisor data, industrial input, daily activities, and other related to the internship.